Awareness and knowledge regarding female genital schistosomiasis among European healthcare workers: a cross-sectional online survey - Valentina Marchese; Aaron Remkes; Irina Kislaya; Pia Rausche; André Brito; Jana Christina Hey; Tahinamandranto Rasamoelina; Rivo Andry Rakotoarivelo; Jürgen May; Daniela Fusco (Globalization and Health)
Abstract Background Adequate knowledge and awareness regarding diseases are essential for appropriate, high-quality healthcare. Female Genital Schistosomiasis (FGS) is a non-sexually transmitted gynaecological disease that is caused by the presence of Schistosoma haematobium eggs in the female genital tract and the resulting immune response that causes tissue damage. It is estimated to affect 56 million women, mostly in sub-Saharan Africa (SSA), where healthcare workers (HCWs) have limited awareness and knowledge of FGS. Most migrants in Europe are female, often from SSA and therefore at risk of FGS. This study investigated awareness and knowledge of FGS among European HCWs with the aim of informing strategies to improve the management of migrant health. Methods We conducted a cross-sectional survey using a self-administered, closed, multilingual, anonymous online questionnaire between 1st June 2023 to 31st January 2024. Medical doctors (MDs) (n = 581) and nurses or midwives (NMs) (n = 341) working in infectiology, gynaecology, urology and general, travel, internal or occupational medicine in European countries were enrolled in the survey. A Poisson regression was used to identify factors associated with MDs’ knowledge and awareness of FGS and adjusted prevalence ratios (aPR) were estimated. Practices related to FGS were described using counts and proportions for a subsample of MDs aware of FGS. Results Among the 922 eligible participants, FGS awareness was 43.7% (CI95%: 39.6; 47.9) for MDs and 12.0% (CI95%: 8.8; 16.0) for NMs. FGS awareness among MDs was higher among men (50.0%; CI95%: 43.7; 56.3), working in clinics for migrants (72.0%, CI95%: 63.2; 79.7) and among infectiologists/travel medicine specialists (68.9%, CI95%: 62.2; 75.0). No knowledge was reported by 67.6% (95% CI 63.7–71.4) of MDs, while 25.3% (CI95%: 21.8; 29.0) had low and 7.1% (CI95%: 5.1; 9.5) medium knowledge. Working in healthcare for migrants was positively associated with medium knowledge (aPR = 3.49; CI95% 1.67;7.28), which was lower for general practitioners (aPR = 0.23, CI95%:0.07;0.81). Conclusions Our study highlights that HCWs in Europe might not be adequately prepared to manage FGS patients, resulting in a high risk of neglect. We believe that the promotion of existing medical networks could improve knowledge about FGS and thus the health of migrant women.